Effects of an Acclimation Protocol During the Handling Events of the 7-day CO-synch + CIDR Protocol on Temperament and Reproductive Performance of Bos taurus Commercial Beef Heifers - Sydney H. Tastad; J. V. C. Silva; Santiago P. Hurtado; A. F. Machado; Victor E. Gomez-Leon; J. Jaeger; N. Oosthuizen; Sandy K. Johnson; Nicholas W. Dias (Kansas Agricultural Experiment Station Research Reports, 2025)
Objective: The objective of this study was to assess the effects of acclimation during the handling events of an estrus synchronization (ES) protocol on temperament and conception rates of commercial beef heifers to timed artificial insemination (TAI). Study Description: Heifers were stratified by reproductive tract score (RTS) and chute score (CS) into the treatment (TRT) or control (CTRL) groups and pastured together. Before each ES event, TRT heifers were sorted, acclimated by sending them through the chute, and commingled with the CTRL heifers. Exit velocity and CS were recorded for all heifers to measure temperament during all ES events. Pregnancy status was determined 40 days post-artificial insemination by rectal ultrasonography. The Bottom Line: Acclimating heifers to the facility during the handling events of the 7-day CO-synch + CIDR estrus synchronization protocol effectively decreased heifer excitability by the time of artificial insemination (Day 10). This study did not support greater reproductive performance of heifers that were acclimated.
Keywords: acclimation; estrus synchronization; beef heifer